PMT Sehat Berbasis Pangan Lokal untuk Mencegah Diare dan Stunting di Desa Mandiro Kabupaten Bondowoso - Setyawati, Julianda; Permatasari, Marshanda Sofi; Pratiwi, Farika Nadiya; Mahdyah, Nafisah Amira; Medisa, Cahya Dhawiya; Agdiansyah, Naufal Thaariq; Al Adzim, Manarul Huday; Maulida, Naila Faricha; Rokhmah, Dewi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Diarrhea can lead to disturbances in nutrient absorption in the body, which may result in growth failure if not promptly addressed. In an effort to prevent diarrhea and stunting in Mandiro Village, the PPK Ormawa HIMA Nutrition FKM UNEJ team provided training on making local food-based supplementary food, specifically chicken-carrot-moringa nugget and chicken-cassava sempol, to Posyandu cadres and mothers of toddlers. The aim of this training is to improve knowledge and understanding the preparation of local food-based supplementary food to address public health issues in Mandiro Village. The training materials were delivered using expositional and demonstrative methods. Monitoring and evaluation of the activities were carried out using pre-test and post-test questionnaires. The pre-test average correct answer rate was 72.2%, while the post-test average correct answer rate was 95.4%. This reflects a 23.2% increase in respondents' knowledge and understanding